2006
DOI: 10.1080/08941930600674694
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Stimulates Wound Healing and Angiogenesis in Mice

Abstract: Erythropoietin exerts hematopoietic effects by stimulating proliferation of early erythroid precursors. Nonhematopoietic effects of erythropoietin have also been shown. It may act as a new angiogenic factor in wound healing. This study aimed to investigate the effect of systemic administration of recombinant human erythropoietin on wound healing in mice. Dorsal incisional wounds were performed in mice, which were then divided into two groups; a group treated for 7 days with recombinant human erythropoietin, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 39 publications
0
27
2
2
Order By: Relevance
“…Further, tissue-specific stem cells are recruited by EPO to take up residence within the region of injury and differentiate into mature, functional cells (32). Finally, EPO also improves collagen deposition and modulates the number of fibroblasts within a wound site (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, tissue-specific stem cells are recruited by EPO to take up residence within the region of injury and differentiate into mature, functional cells (32). Finally, EPO also improves collagen deposition and modulates the number of fibroblasts within a wound site (13).…”
Section: Discussionmentioning
confidence: 99%
“…Among the pleiotropic effects of EPO reported, a number of investigators have reported significant activity of EPO in promoting the healing of ischemic raised cutaneous skin flaps (10)(11)(12)(13)(14), ischemiareperfusion in random musculocutaneous flaps (15), incisional wounds (10,13), and in colonic anastomoses (16,17). Additionally, skin thermal burns also have been reported to respond in a beneficial way to EPO (18).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the cytoprotective role of EPO and have led to its use in the treatment of a number of different disease models such as stroke, surgery and diabetes. [4][5][6] However, the potential role of EPO in the regulation of inflammatory cytokines, in particular by macrophages, has yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…EPO did not affect the VEGF release of HDMEC, but again NHDF were more susceptible to EPO, resulting in an efficient dampening of the VEGF release under hypoxia. Although several authors have described the enhanced expression of VEGF during EPO-mediated healing [8,36], the reduction of the VEGF level detected could also be a useful trigger of NHDF migration. A reduction could especially be important in the case of exorbitantly high VEGF concentrations appearing in the chronic wound as result of intense hypoxia, as it was simulated in the current model.…”
Section: Discussionmentioning
confidence: 91%